2019 IEEE International Conference on Multimedia and Expo (ICME) 2019
DOI: 10.1109/icme.2019.00107
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty-Aware Image Super Resolution via Deep Adaptive Dual-Network

Abstract: Recently, deep learning based single image superresolution(SR) approaches have achieved great development. The state-of-the-art SR methods usually adopt a feed-forward pipeline to establish a non-linear mapping between low-res(LR) and high-res(HR) images. However, due to treating all image regions equally without considering the difficulty diversity, these approaches meet an upper bound for optimization. To address this issue, we propose a novel SR approach that discriminately processes each image region withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…To alleviate this problem, Zhang et al [42] proposed a lightweight ensemble method to improve the generalization of negative correlation learning for regression problems. Qin et al [31] suggested a difficulty-aware image SR method that use a dual-way network to separately recover easy image regions and hard ones. Li et al [23] applied a learning-based adapting method to ensemble the outputs from multiple models, which can exploit the information among successive video frames.…”
Section: Ensemble Strategymentioning
confidence: 99%
“…To alleviate this problem, Zhang et al [42] proposed a lightweight ensemble method to improve the generalization of negative correlation learning for regression problems. Qin et al [31] suggested a difficulty-aware image SR method that use a dual-way network to separately recover easy image regions and hard ones. Li et al [23] applied a learning-based adapting method to ensemble the outputs from multiple models, which can exploit the information among successive video frames.…”
Section: Ensemble Strategymentioning
confidence: 99%
“…Dual-branch Design. Dual-branch network structure design makes use of two branches, complementing each other [8,40,6,45]. It has been used in image super-resolution [40], classification [8], segmentation [6] and person-re-ID [45].…”
Section: Related Workmentioning
confidence: 99%
“…DSRN [43] introduces a dual-state recurrent network to incorporate information from both the LR and the HR spaces. Dual-way SR [17] exploits a complex network EDSR as its complex branch and the bicubic interpolation as its plain branch to capture the global and the detail information. The above dual-path methods design different network structures for different branches to capture more information, but all the branches of these methods are trained with the same loss function.…”
Section: Related Work a Single Image Super-resolutionmentioning
confidence: 99%
“…The feature map is then processed by the sigmoid function to a probability matrix which enables the dual SR framework to yield superior results. Unlike other works that fuse the SR output of each branch to the final output [17], [46], we merge the feature maps in the process of SR image reconstruction which is before the final reconstruction convolution layer. The feature maps extracted from the mask network module is defined as:…”
Section: Mask Networkmentioning
confidence: 99%
See 1 more Smart Citation